The Effectiveness of EXO OLO TASK Learning Model to Improve Students’ Achievement in English Learning - Sherla Chintia Rahmi; Witri Oktavia (Universitas Negeri Padang, 2023)
The objective of this study is to investigate the effectiveness of EXO OLO Task learning model on students’ achievement in English learning. Participants in this study are science eleventh graders at SMAN 1 Kamang Magek. There are 42 students and classified into two classes. The control group is XI MIPA 1. This class consists of 21 students. The experimental group is XI MIPA 2, consists of 21 students. In this study, the researcher employed total sampling. The study was conducted over eight meetings and the experimental class chosen was XI MIPA 2. The essay test was used as the primary data collection tool. The dataset initially comprised 23 questions. However, during the validity and reliability assessments, three questions were identified as invalid and subsequently revised by the researcher. The two-tailed t-test result indicated a significance value of 0.000, meaning the significance value was below 0.05. Therefore, the null hypothesis H0 could not be accepted and the alternative hypothesis H1 could be accepted. This indicates an enhancement in students' English learning outcomes through the utilization of the EXO OLO Task learning model.